Skeletal muscle in MuRF1 null mice is not spared in low-gravity conditions, indicating atrophy proceeds by unique mechanisms in space - Samuel M. Cadena (Nature Portfolio, 2019)
Abstract Microgravity exposure is associated with loss of muscle mass and strength. The E3 ubiquitin ligase MuRF1 plays an integral role in degrading the contractile apparatus of skeletal muscle; MuRF1 null (KO) mice have shown protection in ground-based models of muscle atrophy. In contrast, MuRF1 KO mice subjected to 21 days of microgravity on the International Space Station (ISS) were not protected from muscle atrophy. In a time course experiment microgravity-induced muscle loss on the ISS showed MuRF1 gene expression was not upregulated. A comparison of the soleus transcriptome profiles between spaceflight and a publicly available data set for hindlimb suspension, a claimed surrogate model of microgravity, showed only marginal commonalities between the models. These findings demonstrate spaceflight induced atrophy is unique, and that understanding of effects of space requires study situated beyond the Earth’s mesosphere.